Networked Embedded Control Systems: from Modelling to Implementation - Di Benedetto, Maria Domenica; Giordano Pola (arXiv.org, 2013)
Networked Embedded Control Systems are distributed control systems where the communication among plants, sensors, actuators and controllers occurs in a shared network. They have been the subject of intensive study in the last few years. In this paper we survey our contribution to this research topic.